Auyrvedic Management Of Dushivisha (Cumulative Toxicity) In Present Era. - Meena, Sheetal; Sharma, Anita; Kumar, Praveen (International Research Journal of Ayurveda & Yoga, 2024)
The science of life is calledAyurveda. It gives greater importance to promotion of health and prevention of diseases.AshtangaAyurveda, vishavignyana or Agadatantra is one of the important scientific branches of Ayurveda having specific values for Ayurvedic science, society and with including health of society. Agadtantra is one among of the astang of Ayurveda which deals with toxicology.Asgiven in Ayurvedic ancient scince, a poison is a substance which vitiate normal founctioning ofdosha ,dhatu and mala. As Indians are inclining towards western lifestyle, due to changed food habits, man has become lazy and indulges continuously in ratrijagrana and diva swapnadiviharas produces disease. According to Sushruta, visha which on a constant exposure to a particular time (i.e time –is meant a cloudy and windy day, as well as rainy season), place (place-is meant a anupadesha, extensive windy cold rainy place) and diet (i.e. diet- is meant wine, sesamum, kulattha, pulse) as well as constant and regular day-sleep tends to vitiated the dhatus of the body and this poison is consequently known as the dushivisha. As per the definition any substance which has properties of visha and that which is detrimental to the tissue elements on aggravation in favourable condition can be considered as dushivisha.